2015
DOI: 10.1016/j.bbamem.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of commonly used inhibitors of clathrin-mediated and caveolae-dependent endocytosis of G protein–coupled receptors

Abstract: Among the multiple G protein-coupled receptor (GPCR) endocytic pathways, clathrin-mediated endocytosis (CME) and caveolar endocytosis are more extensively characterized than other endocytic pathways. A number of endocytic inhibitors have been used to block CME; however, systemic studies to determine the selectivity of these inhibitors are needed. Clathrin heavy chain or caveolin1-knockdown cells have been employed to determine the specificity of various chemical and molecular biological tools for CME and caveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 44 publications
3
64
0
Order By: Relevance
“…Next, we assessed the internalization mechanisms of pep- 15) Therefore, in order to confirm the internalization pathway of peptide 8, the cells were incubated with the tested peptides in the presence of several endocytosis inhibitors (amiloride, 16) an inhibitor of macropinocytosis; nystatin, 17) an inhibitor of caveolae-mediated endocytosis; and sucrose, 18) an inhibitor of clathrin-mediated endocytosis), and the intracellular uptake was measured by flow cytometry (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we assessed the internalization mechanisms of pep- 15) Therefore, in order to confirm the internalization pathway of peptide 8, the cells were incubated with the tested peptides in the presence of several endocytosis inhibitors (amiloride, 16) an inhibitor of macropinocytosis; nystatin, 17) an inhibitor of caveolae-mediated endocytosis; and sucrose, 18) an inhibitor of clathrin-mediated endocytosis), and the intracellular uptake was measured by flow cytometry (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Clathrin-mediated and caveolae-dependent pathways are the best-characterized internalization routes of GPCRs (Hansen et al ., 1993; Doherty and McMahon, 2009; Guo et al ., 2015). Clathrin-mediated endocytosis (CME) is initiated by the formation of specialized membrane regions called clathrin-coated pits, into which cell-surface receptors concentrate and form clusters.…”
Section: Selective Regulation Of Clathrin-mediated and Caveolae-depenmentioning
confidence: 99%
“…In a recent study, clathrin heavy chain- or caveolin1-knockdown cells were employed to determine the specificity of various chemical and molecular biological tools for CME and caveolar endocytosis (Guo et al ., 2015). The study showed that sucrose, concanavalin A (Con A), and dominant-negative mutants of dynamin blocked other endocytic pathways, as well as the clathrin-mediated pathway.…”
Section: Selective Regulation Of Clathrin-mediated and Caveolae-depenmentioning
confidence: 99%
See 2 more Smart Citations